Introduction to Responsible Agricultural Investment - UNCTAD; World Bank (World Bank, Washington, DC, 2018)
The United Nation Conference on Trade and Development (UNCTAD) - World Bank knowledge into action note series is a compendium of practical, thematic guidance documents for use by governments, investors, and other stakeholders in the implementation of responsible agricultural investment principles. This document provides background to the knowledge into action note series and the underlying research; it also explains the logic, structure, and sequence of the notes, and suggests some guidance for their use.